World Bank Research Digest, Vol. 4(1) - World Bank (Washington, DC, 2014)
In this issue: changing the climate for development; focus: foreign direct investment (FDI) protectionism on the rise; do poorer countries have less capacity for redistribution? Does trade credit substitute for bank credit during a financial crisis? Demographic and socioeconomic patterns of HIV/AIDS prevalence in Africa; making (more) sense of subjective rankings; and legacy of the caste system in the enforcement of norms.